Ibrutinib plus fludarabine, cyclophosphamide, and rituximab as initial treatment for younger patients with chronic lymphocytic leukaemia: a single-arm, multicentre, phase 2 trial. Issue 8 (August 2019) - Davids, Matthew S; Brander, Danielle M; Kim, Haesook T; Tyekucheva, Svitlana; Bsat, Jad; Savell, Alexandra; Hellman, Jeffrey M; Bazemore, Josie; Francoeur, Karen; Alencar, Alvaro; Shune, Leyla; Omaira, Mohammad; et al.
Summary: Background: Fludarabine, cyclophosphamide, and rituximab (FCR) can improve disease-free survival for younger (age ≤65 years) fit patients with chronic lymphocytic leukaemia with mutated IGHV . However, patients with unmutated IGHV rarely have durable responses. Ibrutinib is active for patients with chronic lymphocytic leukaemia irrespective of IGHV mutation status but requires continuous treatment. We postulated that time-limited ibrutinib plus FCR would induce durable responses in younger fit patients with chronic lymphocytic leukaemia. Methods: We did a multicentre, open-label, non-randomised, single-arm phase 2 trial at seven sites in the USA. We enrolled patients aged 65 years or younger with previously untreated chronic lymphocytic leukaemia. Our initial cohort (original cohort) was not restricted by prognostic marker status and included patients who had del(17p) or TP53 aberrations. After a protocol amendment (on March 21, 2017), we enrolled an additional cohort (expansion cohort) that included patients without del(17p). Ibrutinib was given orally (420 mg/day) for 7 days, then up to six 28-day cycles were administered intravenously of fludarabine (25 mg/m 2, days 1–3), cyclophosphamide (250 mg/m 2, days 1–3), and rituximab (375 mg/m 2 day 1 of cycle 1; 500 mg/m 2 day 1 of cycles 2–6) with continuous oral ibrutinib (420 mg/day). Responders continued on ibrutinib maintenance for up to 2 years, and patients with undetectable minimal residual disease in bone marrow after 2 years were able to discontinue treatment. The primary endpoint was the proportion of patients who achieved a complete response with undetectable minimal residual disease in bone marrow 2 months after the last cycle of ibrutinib plus FCR. Analyses were done per-protocol in all patients who received at least one dose of study treatment. This trial is registered with ClinicalTrials.gov (NCT02251548 ) and is ongoing. Findings: Between Oct 23, 2014, and April 23, 2018, 85 patients with chronic lymphocytic leukaemia were enrolled. del(17p) was detected in four (5%) of 83 patients and TP53 mutations were noted in three (4%) of 81 patients; two patients had both del(17p) and TP53 mutations. Median patients' age was 55 years (IQR 50–58). At data cutoff, median follow-up was 16·5 months (IQR 10·6–34·1). A complete response and undetectable minimal residual disease in bone marrow 2 months after the last cycle of ibrutinib plus FCR was achieved by 28 (33%, 95% CI 0·23–0·44) of 85 patients (p=0·0035 compared with a 20% historical value with FCR alone). A best response of undetectable minimal residual disease in bone marrow was achieved by 71 (84%) of 85 patients during the study. One patient had disease progression and one patient died (sudden cardiac death after 17 months of ibrutinib maintenance, assessed as possibly related to ibrutinib). The most common all-grade toxic effects were haematological, including thrombocytopenia in 63 (74%) patients, neutropenia in 53 (62%), and anaemia in 41 (49%). Grade 3 or 4 non-haematological serious adverse events included grade 3 atrial fibrillation in three (4%) patients and grade 3 Pneumocystis jirovecii pneumonia in two (2%). Interpretation: The proportion of patients who achieved undetectable minimal residual disease in bone marrow with ibrutinib plus FCR is, to our knowledge, the highest ever published in patients with chronic lymphocytic leukaemia unrestricted by prognostic marker status. Ibrutinib plus FCR is promising as a time-limited combination regimen for frontline chronic lymphocytic leukaemia treatment in younger fit patients. Funding: Pharmacyclics and the Leukemia & Lymphoma Society.